2013
DOI: 10.1039/c3tc31314j
|View full text |Cite
|
Sign up to set email alerts
|

Giant optical limiting effect in Ormosil gel glasses doped with graphene oxide materials

Abstract: Graphene materials have attracted interest in the field of optical limiting because of their outstanding linear and nonlinear optical (NLO) properties. However, poor solubility and agglomeration have limited the practical applications of these materials. Here, hydrophilic graphene oxide materials, including graphene oxide nanosheets (GONSs) and graphene oxide nanoribbons (GONRs) are synthesized. Using a facile sol-gel process, GONSs and GONRs are introduced into a methyltriethoxysilane modified silicate (Ormos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(54 citation statements)
references
References 43 publications
2
52
0
Order By: Relevance
“…Zhan and co-workers reported the efficient synthesis of graphene embedded in sol-gel Ormosil glasses. [376,377] They used both nanosheets (GONSs) and nanoribbons (GONRs) (Figure 32). The prepared materials showed high linear transmission in the visible, good thermostability and good optical limiting response attributed to both nonlinear scattering and nonlinear absorption.…”
Section: Graphene Based Hybrid Materials For Nonlinear Absorptionmentioning
confidence: 99%
“…Zhan and co-workers reported the efficient synthesis of graphene embedded in sol-gel Ormosil glasses. [376,377] They used both nanosheets (GONSs) and nanoribbons (GONRs) (Figure 32). The prepared materials showed high linear transmission in the visible, good thermostability and good optical limiting response attributed to both nonlinear scattering and nonlinear absorption.…”
Section: Graphene Based Hybrid Materials For Nonlinear Absorptionmentioning
confidence: 99%
“…63 To investigate materials with significant nonlinear scattering, the Z-scan has been augmented by placing a secondary detector off-axis. 37,64 Consider also, in measurements of nonlinearly scattered radiation, that the scattering might not be spherically homogenous. 65 For certain materials, an integrating sphere intensity scanning measurement is preferable.…”
Section: Z-scanmentioning
confidence: 99%
“…A stringent definition of damage is that no decrease of transmission is detected during several pulses on the same spot while also finding no damage in microscopy images. 37 This method is preferable for separating RSA from damage mechanisms. Other methods include photophysical measurements indicating RSA and ensuring that the nonlinear scattering from glass damage is low.…”
Section: Intensity Scanningmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous reports, Zheng et al made the gold nano-particles/GO into Ormosil glasses by physical mixture of silane sol-gel and gold nano-particles/GO composites and found these glasses have nonlinear absorption and scattering effects under a 532 nm laser [21]. Zhan prepared GO Ormosil glasses at 0.03% by mixing GO with silane sol and found that they have nonlinear absorption and scattering under nanosecond and picosecond pulse lasers [24,25]. These works have obviously confirmed that graphene or GOs could be composited into sol-gel matrix by physical mixture.…”
Section: Introductionmentioning
confidence: 99%